Myofibroblast-Derived Exosome Induce Cardiac Endothelial Cell Dysfunction - Ranjan, Prabhat; Kumari, Rajesh; Goswami, Sumanta Kumar; Li, Jing; Pal, Harish; Suleiman, Zainab; Cheng, Zhongjian; Krishnamurthy, Prasanna; Kishore, Raj; Verma, Suresh Kumar (Frontiers in Cardiovascular Medicine, 2021)
Background: Endothelial cells (ECs) play a critical role in the maintenance of vascular homeostasis and in heart function. It was shown that activated fibroblast-derived exosomes impair cardiomyocyte function in hypertrophic heart, but their effect on ECs is not yet clear. Thus, we hypothesized that activated cardiac fibroblast-derived exosomes (FB-Exo) mediate EC dysfunction, and therefore modulation of FB-exosomal contents may improve endothelial function. Methods and results: Exosomes were isolated from cardiac fibroblast (FB)-conditioned media and characterized by nanoparticle tracking analysis and electron microscopy. ECs were isolated from mouse heart. ECs were treated with exosomes isolated from FB-conditioned media, following FB culture with (TGF-β1-FB-Exo) or PBS (control) treatment. TGF-β1 significantly activated fibroblasts as shown by increase in collagen type1 1 (COL1α1), periostin (POSTN) and fibronectin (FN1) gene expression and increase in Smad2/3 and p38 phosphorylation. Impaired endothelial cell function (as characterized by a decrease in tube formation and cell migration along with reduced VEGF-A, Hif1α, CD31 and angiopoietin1 gene expression) was observed in TGF-β1-FB-Exo treated cells. Furthermore, TGF-β1-FB-Exo treated ECs showed reduced cell proliferation and increased apoptosis as compared to control cells. TGF-β1-FB-Exo cargo analysis revealed an alteration in fibrosis-associated miRNAs, including a significant increase in miR-200a-3p level. Interestingly, miR-200a-3p inhibition in activated FBs, alleviated TGF-β1-FB-Exo-mediated endothelial dysfunction. Conclusions: Taken together, this study demonstrates an important role of miR-200a-3p enriched within activated fibroblast-derived exosomes on endothelial cell biology and function.